Financial development, trade openness, and economic growth in central Asian countries - Vaighan, Behzad Mahmoudi; Kazemi, Morteza; Nezakati, Hossein *; Nia, Atefah Haghighi (2010)
There is a strong debate on the subject of whether financial development led economic growth. The studies that investigated the role of financial development on economic growth consider to different proxies for the variable of financial development and various scopes. Recently, availability of new data set causes an interest subject to study the role of financial development in selected Central Asian countries. Accordingly, this study investigates the relationship among financial development, trade openness and economic growth for seven developing countries in the Central Asian countries over 1993- 2008. Using panel data methods we find a positive and significant bilateral relationship between financial development and economic growth, however the relationship between trade openness and growth does not consist with related theories.